The effects of menstrual and menopausal factors on bone mineral content in healthy Polish women - Szklarska, Alicja; Jankowska, Ewa; Łopuszańska, Monika (Polskie Towarzystwo Antropologiczne, 2002)
The aims of the study were the following: (1) An evaluation of which factor, aging itself or the occurence of menopause, revealed a more detrimental effect on bone mineral content (BMC) of healthy women; (2) An assesment of influence of other factors (the menarcheal age, the total number of reproductive years and the lenght of the period after menopause) on BMC. Our sample material comprised a group of 928 healthy females (715 pre- and 213 postmenopausal), aged 20-62. BMC at the ultra-distal radius was assessed by pQCT. BMC differences between particular groups were tested using a two-way ANOVA. The menopause was related to BMC decline and the impact of menopausal hormonal alterations was much stronger than that of chronological age. Among postmenopausal women, the total number of reproductive years was not an independent predictor of better bone status. In premenpausal women the beneficial effect of earlier menarche on bone tissue is maintained.
Keywords: BMC; osteoporosis; menarcheal age; age at menopause; female aging